Awareness and Acceptability of pre-exposure prophylaxis (PrEP) among gay, bisexual and other men who have sex with men (GBMSM) in Kenya - Ogunbajo, Adedotun (AIDS Care, 2019)
Kenyan gay, bisexual, and other men who have sex with men (GBMSM) are significantly affected by HIV. Pre-exposure prophylaxis (PrEP) is an effective biomedical approach to HIV prevention. We conducted a cross-sectional survey of 459 HIV negative Kenyan GBMSM to assess individual and interpersonal correlates of PrEP awareness/acceptability using univariate and hierarchical logistic regression models. 64.3% of participants had heard of PrEP and 44.9% were willing to use PrEP. In hierarchical logistic regression models for PrEP awareness, condom use with regular partners, higher condom use self-efficacy, higher perceived ability to use PrEP, history of STI, and membership in LGBT organization were significantly associated with being aware of PrEP (χ(2)=69.6, p<0.001). In hierarchical logistic regression models for PrEP acceptability, higher self-esteem, higher condom use self-efficacy, depression/anxiety, higher perceived ability to use PrEP, willingness to engage in PrEP follow-up visits, coercion at sexual debut, and family exclusion were significantly associated with being acceptable to PrEP (χ(2)=231.8, p<0.001). Individual and interpersonal factors were significantly associated with PrEP awareness and acceptability. Our findings underscore the need to promote awareness and understanding of PrEP as an effective HIV prevention tool in combination with other safer-sex methods that are appropriate given an individual’s personal circumstances.